Directed Palladium Catalyzed C−H (Ethoxycarbonyl)difluoromethylthiolation Reactions. Issue 64 (13th September 2022) - Doche, Floriane; Escudero, Julien; Petit‐Cancelier, Fabien; Xiong, Heng‐Ying; Couve‐Bonnaire, Samuel; Audisio, Davide; Poisson, Thomas; Besset, Tatiana
Abstract: The unprecedented Pd‐catalyzed (ethoxycarbonyl)difluoromethylthiolation reaction of various unsaturated derivatives was studied. In the presence of the (ethoxycarbonyl)difluoromethylsulfenamide reagent I and under mild reaction conditions (60 °C), both 2‐(hetero)aryl and 2‐(α‐aryl‐vinyl)pyridine derivatives were smoothly functionalized with this methodology (37 examples, up to 87 % yield). Moreover, the synthetic interest of this fluorinated moiety was further showcased by its conversion into various original fluorinated residues. Finally, a plausible mechanism for this transformation was suggested. Abstract : The unprecedented construction of a C(sp 2 )‐SCF2 CO2 Et bond was successfully achieved by Pd‐catalyzed C−H bond activation. This robust protocol allowed the functionalization of a broad panel of aromatic and olefinic derivatives (37 examples, up to 87 % yield), a real advance as existing routes were restricted to the SCF3 and SCF2 H residues. Post‐functionalization reactions further illustrated the synthetic value of this fluorinated motif.